EFEKTIVITAS LATIHAN INTERVAL SPRINT TERHADAP PENINGKATAN VO2 MAX PADA ANAK USIA 14 TAHUN DI SSB PORASDA GRESIK - Muhammad Satria Prayoga; Dita Yuliastrid (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
VO2 max capacity is a key determinant of soccer players’ physical performance in maintaining game intensity. Sprint interval training is one method used to improve aerobic fitness in young athletes. This study aims to determine the effectiveness of sprint interval training in improving VO2 max capacity in 14 yearold soccer players at SSB Porasda Gresik. This study employed an experimental design with a one-group pretest-posttest measurement. Data were collected from 14 year old players to observe changes in aerobic capacity before and after the training intervention. Data analysis utilized statistical tests and N-Gain calculations to measure the level of effectiveness of the improvement. The results showed a significant increase in the average VO2Max value from 43.02 to 45.09, with a significance level of 0.000 < 0.05. However, based on the N-Gain calculation, the level of effectiveness of this improvement remained in the low category. Sprint interval training was proven to be significantly effective in increasing players’ VO2Max; however, the resulting improvement was not yet optimal. To achieve more optimal results, further development is needed regarding the duration, frequency, and consistency of the training program so that the players’ physiological adaptation can be maximized.